A Novel Technique to Assess Soft-Tissue Redundancy Over the Proximal Interphalangeal Joint - Justine S. Kim, MD; Alexandria A. Bosetti, BS; Elizabeth M. Kenny, MD; Nia Buckner, MSc; Samantha Maliha, MD, MS; Mark E. Baratz, MD (Journal of Hand Surgery Global Online)
Purpose: Loss of redundant soft tissue over the proximal interphalangeal joint (PIPJ) may be a reason for the failed restoration of PIP motion. This study aimed to quantify the area of redundant skin over the PIPJ in normal subjects. Methods: Measurements of 200 healthy volunteers were obtained using a novel technique. Redundant skin over the PIPJ was pinched and marked in a radial-to-ulnar, then proximal-to-distal direction with the PIPJ extended. The area of skin overlying the PIPJ was calculated for the index, middle, ring, and small fingers. A standardized ratio was developed to provide a normative scale to compare post-traumatic skin redundancy. Results: The study population included 82 men and 118 women. Demographics including average height, weight, body mass index (BMI), smoking status, and hand dominance were collected. Skin redundancy or area of skin (mm2) overlying the PIPJ was calculated for bilateral index, middle, ring, and small fingers. Skin redundancy was greater in ring fingers of men compared with those of women. Skin redundancy was examined between BMI greater than 30 and less than 30 and found to be statistically different in the middle, ring, and small fingers. Normative values for skin redundancy by percentiles for each gender and BMI were generated. Conclusions: Establishment of normative values may enable surgeons to explain the lack of progress after surgical joint release, determine progress with hand therapy, and choose the optimal timing of surgical intervention once soft-tissue equilibrium is achieved. Type of study/level of evidence: Prognostic III.